PEMBELAJARAN MODEL TEAMS GAMES TOURNAMENT DENGAN MEDIA ENGKLUT (ENGKLEK ULAR TANGGA) PADA PEMBELAJARAN MATEMATIKA - Deivy Adityas Kurniawati (Universitas Asahan, 2019)
This study aims to describe the increase in mathematics learning outcomes through the Teams Games Tournament (TGT) learning model with ENGKLUT media (Ladder Snake Englage) in quadrilateral material in class VII Muhammadiyah 5 Surabaya Middle School, amounting to 24 students. This type of research is Class Action Research (CAR). The data collection techniques used are observation techniques, questionnaire techniques, test techniques. The instruments used were the Learning Implementation Plan (RPP), teaching materials, student worksheets (LKS), ENGKLUT media, student activity observation sheets, student response questionnaire sheets, learning outcomes test questions. The results showed that (1) The value before the study increased in the first cycle with an average of 74.92, then increased from cycle I to cycle II with an average of 86.44. (2) The average value of student activity from cycle I to cycle II has increased by 2.25%. (3) Students' responses to learning are shown with the percentage of responses